2017
DOI: 10.1002/ajmg.a.38566
|View full text |Cite
|
Sign up to set email alerts
|

Small supernumerary marker chromosome 15 and a ring chromosome 15 associated with a 15q26.3 deletion excluding the IGF1R gene

Abstract: Array comparative genomic hybridization is essential in the investigation of chromosomal rearrangements associated with epilepsy, intellectual disability, and dysmorphic features. In many cases deletions, duplications, additional marker chromosomes, and ring chromosomes originating from chromosome 15 lead to abnormal phenotypes. We present a child with epilepsy, cardiac symptoms, severely delayed mental and growth development, behavioral disturbances and characteristic dysmorphic features showing a ring chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…We identified that there is a common breakpoint in most: the genomic region 15q26. Duplication, deletions, and gains in this region could be associated with different phenotypic manifestations as the region harbors different genes [ 15 ]. For instance, insulin-like growth factor 1 receptor ( IGF1R ) is involved in normal growth and development [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified that there is a common breakpoint in most: the genomic region 15q26. Duplication, deletions, and gains in this region could be associated with different phenotypic manifestations as the region harbors different genes [ 15 ]. For instance, insulin-like growth factor 1 receptor ( IGF1R ) is involved in normal growth and development [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of the 15q26.2qter region, for instance, have been described in a few patients with intrauterine and postnatal growth retardation, congenital heart defects, intellectual disability, triangular facial shape, skeletal anomalies such as clinodactyly and brachydactyly, and other minor abnormalities related to the shape of the nasal bridge and the eyes [Rump et al, 2008;Ester et al, 2009;Rudaks et al, 2011;Poot et al, 2013;O'Riordan et al, 2017;Szabó et al, 2018;Santos et al, 2020]. Haploinsufficiency of the IGF1R gene has been postulated as the main cause of most of these clinical features since they are similar to the ones caused by single mutations in this gene [Walenkamp et al, 2008] as well as its partial deletion [Veenma et al, 2010], especially in regard to growth deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We could not properly evaluate this patient, but his blood samples were collected for karyotype. Pinson et al, 2005;Rujirabanjerd et al, 2007;Rump et al, 2008;Walenkamp et al, 2008;Ester et al, 2009;Bruce et al, 2010;Lin et al, 2010;Dateki et al, 2011;Rudaks et al, 2011;Poot et al, 2013;O'Riordan et al, 2017;Santos et al, 2020. b Lucaccioni et al, 2015;Szabó et al, 2018;DECIPHER: 270050, 265742, 401263, 251400, 353687, 331451, 331238, 286496, 280979. c Chia et al, 1987;Webb et al, 1988;Rethoré et al, 1989;Zenger-Hain et al, 1993;Chen et al, 1995;Baialardo et al, 2003;Cervera et al, 2005. Bellucco/Favilla/Perrone/Melaragno Cytogenet Genome Res 2020;160:589-596 592 DOI: 10.1159/000511235…”
Section: Patient 3 (Iii-12)mentioning
confidence: 99%
See 2 more Smart Citations